Sources of Perceived Social Support, Social-Emotional Experiences, and Psychological Well-Being of International Students. Issue 1 (2nd January 2021) - Brunsting, Nelson C.; Zachry, Corinne; Liu, Jintong; Bryant, Rhonda; Fang, Xuanyu; Wu, Siyu; Luo, Zhengda
Abstract: To advance understanding of international students' psychological well-being and social-emotional experiences, we tested whether specific social influences could enhance international students' belonging and well-being and attenuate loneliness. Graduate and undergraduate international students ( N = 126) from two universities in the United States participated in a year-long study. Structural equation modeling analyses revealed that perceived social support from domestic students in the fall predicted higher belonging in the subsequent spring, while perceived faculty social support in the fall predicted lower loneliness in the spring. Perceived faculty social support had an indirect effect on psychological well-being via loneliness. These novel findings provide initial evidence for the salience of social support from domestic students and faculty for international students' social-emotional adjustment.